The Abandoned City and the City Rediscoved. The Fate of St. Sergius of Radonezh and Other Fathers of the Russian Church - Olga Viktorovna Kireeva (Управленческое консультирование)
The article is devoted to the Genesis of monasticism in Ancient Russia as the earliest form of deurbanization in Russian culture. The reasons of the rejection of mundane life, the creation of monasteries accoding to the image of the “heavenly city” and causes the return of the monks to the city “sinful” are analysed, the forms of monasticism, the fate of the hermits and monks in extant sources are considered.